Characteristic of nitrous oxide production in partial denitrification process with high nitrite accumulation. (March 2016) - Du, Rui; Peng, Yongzhen; Cao, Shenbin; Wang, Shuying; Niu, Meng
Highlights: N2 O production in partial denitrification with high NO2 − -N accumulated was studied. N2 O production could be ignored during NO2 − -N accumulation before NO3 − -N depletion. Accumulation of N2 O was strongly related to the NO2 − -N reduction process. Low pH condition significantly enhanced N2 O production. N2 O production could be alleviated by controlling pH turning point. Abstract: Nitrous oxide (N2 O) production during the partial denitrification process with nitrate (NO3 − -N) to nitrite (NO2 − -N) transformation ratio of 80% was investigated in this study. Results showed that N2 O was seldom observed before complete depletion of NO3 − -N, but it was closely related to the reduction of NO2 − -N rather than NO3 − -N. High COD/NO3 − -N was in favor of N2 O production in partial denitrification with high NO2 − -N accumulation. It was seriously enhanced at constant acidic pH due to the free nitrous acid (FNA) inhibition. However, the N2 O production was much lower at initial pH of 5.5 and 6.5 due to the pH increase during denitrification process. Significantly, the pH turning point could be chosen as a controlled parameter to denote the end of NO3 − -N reduction, which could not only achieve high NO2 − -N accumulation but also decrease the N2 O production significantly for practical application.